2001
DOI: 10.4315/0362-028x-64.7.1019
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Essential Oils from Plants against Selected Pathogenic and Saprophytic Microorganisms

Abstract: The beneficial health effects of extracts from many types of plants that are used as seasoning agents in foods and beverages have been claimed for centuries. The purpose of this study was to examine the effectiveness of selected herb and spice essential oils for control of growth and survival of microorganisms. Inhibition of growth was tested by the paper disc agar diffusion method. Antibiotic susceptibility discs were used as control. Minimum lethal concentration (MLC) was determined by the tube dilution meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
277
5
14

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 502 publications
(310 citation statements)
references
References 14 publications
14
277
5
14
Order By: Relevance
“…The differences might be attributed to inherent factors of the oil such as preharvest factors (e.g. variety, ambient conditions, and ecological factors) and differences in oil extraction methods (ELGAYYAR et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The differences might be attributed to inherent factors of the oil such as preharvest factors (e.g. variety, ambient conditions, and ecological factors) and differences in oil extraction methods (ELGAYYAR et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…They found that pepper, nutmeg, rosemary and garlic decreased the maximum specific growth rate of L. curvatus while paprika was the only spice that increased its growth. Essential oils obtained from coriander, angelica and parsley were not effective against L. plantarum (Elgayyar, Draughon, Golden, & Mount, 2001), while the essential oils of five different varieties of basil possessed mild antimicrobial activity (Lachowicz et al, 1998).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Some authors have demonstrated a linear correlation between the content of total phenolic compounds and their antioxidant activity (Djeridane, Yousfi, Nadjemi, Boutassouna, Stocker, & Vidal, 2006;Wong, Leong, & Koh, 2006). Extracts from spices and herbs are also effective in prolongation of the shelf life of food products through the reduction in growth of pathogenic and spoilage microorganisms (Elgayyar, Draughon, Golden, & Mount, 2001). Some spices such as garlic and cardamom are also used for the production of fermented foodstuffs, especially dairy and meat products (Verluyten, Leroy, & Vuyst, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of anise oil as an antifungal agent was also reported in 2001 [16]. Main component of anise oil (trans-anethole), is believed to be the main inhibitory component [17].…”
Section: B Decay Test On Rubberwoodmentioning
confidence: 99%